Evaluation of a recombinant nucleocapsid protein‐based assay for Anti‐SARS‐CoV IgG detection - Chan, Paul K.S. (J Med Virol, 2004)
A high throughput accurate assay for anti‐SARS‐CoV IgG detection is needed for large‐scale epidemiological studies. The evaluation of a commercial recombinant nucleocapsid protein‐based microtitre plate enzyme immunoassay, ELISARS™ is described. The results on 150 sera from SARS patients and 450 sera from non‐SARS controls showed that this assay had a high level of sensitivity (96.2% for late serum samples) and specificity (97.8%). The performance and setup of this assay fulfills the requirement as a screening test for large‐scale studies. A vast majority of SARS patients developed antibodies against the nucleocapsid protein. In some patients (10/45), a high level of anti‐nucleocapsid antibody appeared very early in the course of the illness. In contrast, a minority (4 of 105 patients) never developed these antibodies. The implication of differences in antibody response to the nucleocapsid protein deserves further investigation. J. Med. Virol. 75:181–184, 2005. © 2004 Wiley‐Liss, Inc.